Recombinant production of eukaryotic cytochrome P450s in microbial cell factories. Issue 2 (5th March 2018) - Hausjell, Johanna; Halbwirth, Heidi; Spadiut, Oliver
Abstract : Cytochrome P450s (P450s) comprise one of the largest known protein families. They occur in every kingdom of life and catalyze essential reactions, such as carbon source assimilation, synthesis of hormones and secondary metabolites, or degradation of xenobiotics. Due to their outstanding ability of specifically hydroxylating complex hydrocarbons, there is a great demand to use these enzymes for biocatalysis, including applications at an industrial scale. Thus, the recombinant production of these enzymes is intensively investigated. However, especially eukaryotic P450s are difficult to produce. Challenges are faced due to complex cofactor requirements and the availability of a redox-partner (cytochrome P450 reductase, CPR) can be a key element to get active P450s. Additionally, most eukaryotic P450s are membrane bound which complicates the recombinant production. This review describes current strategies for expression of P450s in the microbial cell factories Escherichia coli, Saccharomyces cerevisiae, and Pichia pastoris .